Reprogramming Immune Cells for Enhanced Cancer Immunotherapy: Targets and Strategies - Dong, Yan; Wan, Zhuo; Gao, Xiaotong; Yang, Guodong; Liu, Li (Frontiers in Immunology, 2021)
Cancer is one of the leading causes of death and a major public health problem all over the world. Besides the traditional cancer therapies, such as surgery, radiotherapy, and chemotherapy, immunotherapy is becoming a revolutionary clinical management for various cancer types. Restoration of aberrant immune surveillance on cancers has been achieved markable progress in the past years by either in vivo or ex vivo engineering of the immune cells. Here, we summarized the central roles of immune cells in tumor progression and regression, and the existing and emerging immunotherapy strategies for different immune cells. In addition, the current challenges and the potential solutions in translating the promising immunotherapy into clinic are also discussed.